The Effect Of Cowbean Flour Substitution (Unguiculata Vine) On The Physical Quality And Sensory Quality Of Hidden Peanuts - Irva, Nurul Maghfirah; Riska, Nur; Sachriani, Sachriani (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the effect of cowpea flour substitution on the physical quality and sensory attributes of kacang sembunyi (hidden peanuts). The research was conducted at the Pastry and Bakery Laboratory of the Culinary Arts Education Study Program, Universitas Negeri Jakarta, from May 2024 to August 2025. An experimental method was used in this study. The samples were kacang sembunyi with cowpea flour substitution at concentrations of 10%, 20%, and 30%. These samples were then tested on 45 semi-trained panelists who evaluated all aspects of sensory quality. The results showed that cowpea flour substitution had a significant effect on physical quality tests. The Duncan test results indicated a significant difference in the aspects of cooking loss and oil absorption capacity. The highest mean value for Cooking Loss was found in the 30% treatment 15.50, while the highest mean for oil absorption capacity was found in the 10% treatment 12.43. The Kruskal-Wallis test indicated that the substitution of cowpea flour did not affect the sensory attributes of color, aroma, taste, and texture. This study recommends the 30% cowpea flour substitution for further development as an effort to optimize the utilization of cowpea as a local food ingredient.